2018
DOI: 10.1139/cjps-2017-0241
|View full text |Cite
|
Sign up to set email alerts
|

Tank mixture of glyphosate with 2,4-D accentuates 2,4-D injury in glyphosate-resistant corn

Abstract: Six field trials were conducted at Ridgetown, ON, over a 2-yr period (2015 and 2016) to determine the tolerance of two corn hybrids to 2,4-D (560 and 1120 g a.i. ha−1) and glyphosate (1800 g a.e. ha−1) applied alone or in combination at stage V1, V3, or V5. In DeKalb DKC52-61 corn, 2,4-D caused as much as 24%, 16%, 11%, and 11% visible injury at 1 wk after each postemergence herbicide application (WAT), 2 WAT, 4 wk after the last postemergence herbicide application (WA-C), and 8 WA-C, respectively. Plant stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
0
17
2
Order By: Relevance
“…Metzger et al [47] found tolpyralate + atrazine + MSO + UAN to have a wide margin of crop safety on some commonly used corn hybrids in Ontario when used according to label recommendations, although environmental variables may affect corn injury levels. In contrast to research by Soltani et al [34] that reported increased crop injury when glyphosate was added to 2,4-D, the addition of glyphosate to tolpyralate + atrazine did not enhance crop injury. Any visible crop injury symptoms in these studies did not affect corn yield.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Metzger et al [47] found tolpyralate + atrazine + MSO + UAN to have a wide margin of crop safety on some commonly used corn hybrids in Ontario when used according to label recommendations, although environmental variables may affect corn injury levels. In contrast to research by Soltani et al [34] that reported increased crop injury when glyphosate was added to 2,4-D, the addition of glyphosate to tolpyralate + atrazine did not enhance crop injury. Any visible crop injury symptoms in these studies did not affect corn yield.…”
Section: Discussioncontrasting
confidence: 99%
“…Armel et al [52] also reported improved control of common ragweed and giant foxtail with mesotrione (105 or 140 g•ai•ha −1 ) when in a tankmix with glyphosate compared to mesotrione alone. Soltani et al [34] reported an interaction between glyphosate and 2,4-D where corn injury is enhanced with the addition of glyphosate, speculated to be caused by the aggressive adjuvant system in a commercial glyphosate formulation. In contrast to results from Soltani et al [34], crop injury was not accentuated with the addition of glyphosate to tolpyralate + atrazine, however there was an influence on weed control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glyphosat and 2,4 -D herbicides have a different mechanism but a mixture of both had been reported compatible and showed a synergistic effects on the target weeds (Wehtje and Gilliam, 2012). Mixures of these two herbicides may increase herbicide efficacy, reduce a dose of application either on glyphosate or 2,4-D, and also prevent the evolve of resistant weeds (Robinson et al, 2012;Soltani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%